2001
DOI: 10.1021/jo010355g
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the Liposidomycin Diazepanone Stereochemistry

Abstract: The liposidomycins comprise a family of complex nucleoside antibiotics that inhibit bacterial peptidoglycan synthesis. Their structures (1, 2) feature nucleoside, ribofuranoside, diazepanone, and lipid regions. Several stereogenic centers remain unassigned, including three within the diazepanone region: C-6', C-2'", and C-3'". An intramolecular reductive amination reaction has been used to prepare model diazepanones. Analysis of 40 and two of its diastereomers by NMR spectroscopy, X-ray crystallography, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…More than 8 groups have studied the total synthesis of LPMs. [123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140] Difficulty in the synthesis of this class of molecules may lie with the introduction of 5-aminoribose moiety found in CPZs and LPMs after construction of a uridyldiazepanone moiety because the tertiary amine contained in the diazepanone structure inhibited the usual ribosylation promoted by Lewis acid. In addition, CPZs and LPMs would be sensitive to basic conditions because they contain a b-heterosubstituted carboxyl moiety.…”
Section: -110)mentioning
confidence: 99%
“…More than 8 groups have studied the total synthesis of LPMs. [123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140] Difficulty in the synthesis of this class of molecules may lie with the introduction of 5-aminoribose moiety found in CPZs and LPMs after construction of a uridyldiazepanone moiety because the tertiary amine contained in the diazepanone structure inhibited the usual ribosylation promoted by Lewis acid. In addition, CPZs and LPMs would be sensitive to basic conditions because they contain a b-heterosubstituted carboxyl moiety.…”
Section: -110)mentioning
confidence: 99%
“…3.4) has been investigated by the groups of Knapp [81][82][83] and Ubukata [84,85] through chemical synthesis. Recent studies have indicated that the configuration at C-5' and C-6' are both S [83], and the configuration at C-2''' and C-3''' are also both S [85].…”
Section: Bmentioning
confidence: 99%
“…The configuration of the double bonds of the lipid moiety of liposidomycin A I is cis [22]. The stereoselective synthesis of the disaccharide and 1,4-diazepan-3-one fragments and their comparison with the degradation products of liposidomycin have enabled the determination of configurations [23,24].…”
Section: Natural Disaccharide Nucleosidesmentioning
confidence: 99%